Respostas

2014-07-17T16:04:09-03:00
C) 3x + 2y = 2
2x + 3y = 3 ( -1)

3x + 2y = 2
-2x - 3y = -3

x - y = -1
x = -1 + 4

(Agora substituindo na formula 3x + 2y = 2)

3( -1 + y) + 2y = 2
-3 + 3y + 2y = 2
5y = 2 + 3
5y = 5
y = 5 : 5
y = 1

(Descobrindo o valor de 'x')

3x + 2 . 1 = 2
3x + 2 = 2
3x = 2 - 2
3x = 0
x = 0 : 3
x = 0
d) 4x + 2y = -2
2x + 3y = -7

6x + 5y = -9
5y = -9 + 6x

(Substituindo na formula 4x + 2y = -2)

4x + 2.( -9 + 6x) = -2
4x -18 + 12x = -2
16x = 16
x = 16 :16
x = 1

(Descobrindo o valor de 'y')

4 .1 +2y = -2
4 + 2y = -2
2y = -2 - 4
2y = -6
y = -6 : 2
y = -3